Implications of Exchange Rate Objectives under Incomplete Exchange Rate Pass-Through - Malin Adolfson (Sveriges Riksbank, 2002)
This paper analyzes the central banks optimal objective function in a small open economy model allowing for incomplete exchange rate pass-through. The results indicate that there are welfare gains from different types of monetary policy inertia. The welfare improvements of exchange rate stabilization are, however, dependent on the degree of discretionary stabilization bias. If the stabilization bias has been mitigated through a low weight on output stabilization social welfare can not be improved by inclusion of an explicit exchange rate term in the delegated objective function, irrespective of the degree of pass-through. Welfare can, though, be enhanced by appointing a central banker with greater preference for interest rate smoothing than that of society. The optimal degree of interest rate smoothing is increasing in the degree of pass-through.
Keywords: E52; E58; F41; 330; Exchange rate pass-through; inflation targeting; interest rate inertia; monetary policy; small open economy